On Some Problems of Polynomial Approximation of Entire Transcendental Functions - Vakarchuk, S. B.; Zhir, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For entire transcendental functions of finite generalized order, we obtain limit relations between the growth characteristic indicated above and sequences of their best polynomial approximations in certain Banach spaces (Hardy spaces, Bergman spaces, and spaces \(B( p,q,λ )\) ).